2011
DOI: 10.1111/j.1365-2249.2011.04445.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive functions of hepatic myeloid-derived suppressor cells of normal mice and in a murine model of chronic hepatitis B virus

Abstract: SummaryThe immunosuppressive state of tumour-bearing hosts is attributable, at least in part, to myeloid-derived suppressor cells (MDSC). However, the role of MDSC in physiological conditions and diseases other than cancer has not been addressed. As the liver is a tolerogenic organ, the present study attempted to localize and assess functions of hepatic MDSC in a normal liver and in a murine model of chronic hepatitis B virus (HBV) infection. MDSC was identified in the liver of normal mice and HBV transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
83
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 25 publications
10
83
2
Order By: Relevance
“…Therefore, the precise role of MDSCs in chronic virus infection and their associations with outcome remain elusive. In this study, to our knowledge for the first time, we identified an increase for a population of CD14 + cells that have low or no expression of HLA-DR in a cohort of CHB patients, in agreement with previous studies in HBV transgenic mice and HIV patients (21,22,34). Interestingly, the presence of MDSCs was associated with increased PD-1 expression, suggesting that the immunosuppressive phenotype of MDSCs in CHB patients is CD14 + HLA-DR 2/low PD-1 + .…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the precise role of MDSCs in chronic virus infection and their associations with outcome remain elusive. In this study, to our knowledge for the first time, we identified an increase for a population of CD14 + cells that have low or no expression of HLA-DR in a cohort of CHB patients, in agreement with previous studies in HBV transgenic mice and HIV patients (21,22,34). Interestingly, the presence of MDSCs was associated with increased PD-1 expression, suggesting that the immunosuppressive phenotype of MDSCs in CHB patients is CD14 + HLA-DR 2/low PD-1 + .…”
Section: Discussionsupporting
confidence: 77%
“…It has been reported that MDSCs of diseased mice have an increased capacity to suppress T-cell proliferation compared with MDSCs of normal mice. 28 This is supported by the finding that MDSCs from healthy controls show decreased expression of immunosuppressive molecules compared with MDSCs from cancer patients. 29 Likewise, in a previous study we showed that arginase-1 is expressed in PBMCs in much larger amounts in lung cancer patients than in healthy controls.…”
Section: Discussionsupporting
confidence: 76%
“…However, in mice, MDSCs are also present in the liver during physiological conditions and are thought to play a pivotal role in maintaining homeostasis. 28 Therefore, the function of MDSCs is probably different in healthy controls and cancer patients. It has been reported that MDSCs of diseased mice have an increased capacity to suppress T-cell proliferation compared with MDSCs of normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the S1P1R-signaling pathway, FTY720 potentiates MDSC recruitment and function and promotes reciprocal differentiation of Tregs and Th1 cells for protection against hepatic injuries. This is inconsistent with the previously established role for MDSCs in limiting autoimmune hepatic inflammatory injury (45). Our studies reveal a previously unknown feature of MDSC function in liver homeostasis, the reprogramming of T cell differentiation from Th1 cells to iTregs, which represents a novel mechanism of FTY720-mediated protection against immunological hepatic injuries by targeting the S1P receptor-mTOR-signaling pathway.…”
Section: Discussioncontrasting
confidence: 56%